Učinki slovensko-hrvaške meje in osamosvojitve na turizem v hrvaški in slovenski Istri - Gosar, Anton (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2001)
The paper discusses the structure of the tourist economy and analyses visits in the Slovenian part (the tourist region "Obala in Kras") and the Croatian part (Istarska županija) of the Istrian peninsula, in the Northern Adriatic. The discussed time-span 1985 - 1999 falls in the years as Slovenia and Croatia, former republics within the multi-ethnic federation of Yugoslavia, in 1991 declared independence. The rebellion of the Serbs in Croatia (until 1995) and the ongoing conflict in the Balkans have impacted tourism at the most. In addition has the change from the "socialist" to market economy influenced the scene in time of general transition from communism to democracy. This study relates to published data on tourist visits to both regions and towns of Istria. It compares the region in relation to the developments in other parts of the respective states and among each other. The study focuses particular on changes in tourism development strategies, made by the state, due to diverse structures and, finally, financial outcomes of the tourist economies, operating in similar natural and cultural environments. Neither region has yet reached the tourist visits and bed-nights from the years before independence. Croatia falls behind much more than Slovenia. The study states that the Slovenian part is better of due to the proximity to tourist markets and, most obvious, due to new development strategies, adding the 3E experience (Casino, Aqualand) to the Mediterranean image. Very informative are the results, which came from qualitative interviews made by students in several coastal cities of Istria in 1999. They add an additional knowledge to the research both countries have conducted |TOMAS| in 1994 and 1997 in order to improve their image on the global tourist market.
Keywords: Croatia; državne meje; Hrvaška; Istra; Istria; obmejna območja; obmejno sodelovanje; regionalni razvoj; Slovenia; Slovenija; tourism; turistična geografija; turizem